Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

The use of participatory modelling to inform management of endemic foot-and-mouth disease: A case study from Nusa Tenggara Barat, Indonesia - Sandra Steele; Yuni Yupiana; Indri Permatasari; Ratna Vitta Ekowati; Dhony Kartika Nugroho; Anke Wiethoelter; Matthew Edwards; Siti Yulianti; Nurhayati; Ermawanto; Tyas Dwi Utami; Rince Morita Butar Butar; et al. (Preventive Veterinary Medicine, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

An updated Irwin sensor for measurement of surface shear velocity - Nancy P. Ziegler; Nicholas P. Webb; Brandon L. Edwards; George Nikolich; John A. Gillies; Sahil G. Patel; Brandi Wheeler; Pei Zhang; Justin W. Van Zee; Sandra L. LeGrand; Andrew C. Trautz (Aeolian Research, 2026)

Cardiovascular risk factors and vascular neuropathological findings in primary age-related tauopathy versus Alzheimer’s disease - Lisa Y. Xiong; Myuri Ruthirakuhan; Si Won Ryoo; Che-Yuan Wu; Jodi D. Edwards; Jennifer S. Rabin; Maria Carmela Tartaglia; Sandra E. Black; Julia Keith; Walter Swardfager (GeroScience, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Seismic imaging of mid-crustal heterogeneity beneath geothermal systems, central Taupō Volcanic Zone, New Zealand - Stephen Bannister; Edward A. Bertrand; Geoff Kilgour; T. Grant Caldwell; Isabelle Chambefort; Wiebke Heise; Sandra Bourguignon (Journal of Volcanology and Geothermal Research, 2025)

Drifting fish aggregation devices as a tool to study oceanic marine protected areas - Arthur Blanluet; Edward T. Game; Kydd Pollock; Nicholas H. Wolff; Jason D. Everett; Sandra Neubert; Daniel C. Dunn; Anthony J. Richardson (Fisheries Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Potential of nature-based solutions to reduce antibiotics, antimicrobial resistance, and pathogens in aquatic ecosystems. a critical review - Edward J. Pastor-López; Mònica Escolà; Vaidotas Kisielius; Carlos A. Arias; Pedro N. Carvalho; Ana M. Gorito; Sandra Ramos; Vânia Freitas; Laura Guimarães; C. Marisa R. Almeida; Jochen A. Müller; Eberhard Küster; et al. (Science of The Total Environment, 2024)

Risk factors affecting the feeding site predilection of ticks on cattle in Ghana - Seth Offei Addo; Ronald Essah Bentil; Mba-tihssommah Mosore; Eric Behene; Julian Adinkrah; Janice Tagoe; Clara Yeboah; Bernice Olivia Ama Baako; Dorcas Atibila; Sandra Abankwa Kwarteng; Kwaku Poku-Asante; Ellis Owusu-Darbo; et al. (Experimental and Applied Acarology, 2024)
Ticks are important disease vectors affecting animal health and causing substantial economic loss, especially in the tropics and subtropics. To examine the tick burden of cattle and associated risk factors for tick infestation, ticks were collected from 388 cattle within five regions in Ghana. Most of the cattle were males (50.3%) and generally older than 3 years (65%). Of the animals sampled, 2187 ticks were collected with a mean tick burden of 5.6 ticks per cattle, and the average tick burden on the udder/scrotum being significantly higher than in the anal region (Generalized Linear Mix Model [GLMM], p = 0.01197). The tick species identified were predominantly Amblyomma variegatum (42.6%) and Hyalomma rufipes (26.2%). High proportions of cattle examined were found to have A. variegatum infesting the udder/scrotum. Furthermore, H. rufipes infested mostly the anal region compared to other examined body parts (OR 14.8, 95% CI 8.6–25.4, p < 0.001). Using the GLMM, tick abundance was found to be significantly higher in cattle older than 3 years. The tick burden in the udder/scrotum was higher than that from the chest and leg/thigh of the cattle (GLMM, p < 0.05). The tick burden at the anal region was also significantly higher than the leg/thigh and chest. This study indicates that the preferred attachment sites of ticks on cattle are species-dependent and effective treatment with acaricides should take into consideration the udder/scrotum and anal regions as well as prioritizing older cattle.

Accuracy of patient race and ethnicity data in a central cancer registry - Rachel R. Codden; Carol Sweeney; Blessing S. Ofori-Atta; Kimberly A. Herget; Kacey Wigren; Sandra Edwards; Marjorie E. Carter; Rachel D. McCarty; Mia Hashibe; Jennifer A. Doherty; Morgan M. Millar (Cancer Causes & Control, 2024)

Determining the sustainability of legal wildlife trade - Alice Hughes; Mark Auliya; Sandra Altherr; Brett Scheffers; Jordi Janssen; Vincent Nijman; Chris R. Shepherd; Neil D'Cruze; Emerson Sy; David P. Edwards (Journal of Environmental Management, 2023)

Genetic variation of glycophorins and infectious disease - Edward J. Hollox; Sandra Louzada (Immunogenetics, 2023)
Glycophorins are transmembrane proteins of red blood cells (RBCs), heavily glycosylated on their external-facing surface. In humans, there are four glycophorin proteins, glycophorins A, B, C and D. Glycophorins A and B are encoded by two similar genes GYPA and GYPB , and glycophorin C and glycophorin D are encoded by a single gene, GYPC . The exact function of glycophorins remains unclear. However, given their abundance on the surface of RBCs, it is likely that they serve as a substrate for glycosylation, giving the RBC a negatively charged, complex glycan “coat”. GYPB and GYPE (a closely related pseudogene) were generated from GYPA by two duplication events involving a 120-kb genomic segment between 10 and 15 million years ago. Non-allelic homologous recombination between these 120-kb repeats generates a variety of duplication alleles and deletion alleles, which have been systematically catalogued from genomic sequence data. One allele, called DUP4, encodes the Dantu NE blood type and is strongly protective against malaria as it alters the surface tension of the RBC membrane. Glycophorins interact with other infectious pathogens, including viruses, as well as the malarial parasite Plasmodium falciparum , but the role of glycophorin variation in mediating the effects of these pathogens remains underexplored.

SIPN South: six years of coordinated seasonal Antarctic sea ice predictions - François Massonnet; Sandra Barreira; Antoine Barthélemy; Roberto Bilbao; Edward Blanchard-Wrigglesworth; Ed Blockley; David H. Bromwich; Mitchell Bushuk; Xiaoran Dong; Helge F. Goessling; Will Hobbs; Doroteaciro Iovino; et al. (Frontiers in Marine Science, 2023)
Antarctic sea ice prediction has garnered increasing attention in recent years, particularly in the context of the recent record lows of February 2022 and 2023. As Antarctica becomes a climate change hotspot, as polar tourism booms, and as scientific expeditions continue to explore this remote continent, the capacity to anticipate sea ice conditions weeks to months in advance is in increasing demand. Spurred by recent studies that uncovered physical mechanisms of Antarctic sea ice predictability and by the intriguing large variations of the observed sea ice extent in recent years, the Sea Ice Prediction Network South (SIPN South) project was initiated in 2017, building upon the Arctic Sea Ice Prediction Network. The SIPN South project annually coordinates spring-to-summer predictions of Antarctic sea ice conditions, to allow robust evaluation and intercomparison, and to guide future development in polar prediction systems. In this paper, we present and discuss the initial SIPN South results collected over six summer seasons (December-February 2017-2018 to 2022-2023). We use data from 22 unique contributors spanning five continents that have together delivered more than 3000 individual forecasts of sea ice area and concentration. The SIPN South median forecast of the circumpolar sea ice area captures the sign of the recent negative anomalies, and the verifying observations are systematically included in the 10-90% range of the forecast distribution. These statements also hold at the regional level except in the Ross Sea where the systematic biases and the ensemble spread are the largest. A notable finding is that the group forecast, constructed by aggregating the data provided by each contributor, outperforms most of the individual forecasts, both at the circumpolar and regional levels. This indicates the value of combining predictions to average out model-specific errors. Finally, we find that dynamical model predictions (i.e., based on process-based general circulation models) generally perform worse than statistical model predictions (i.e., data-driven empirical models including machine learning) in representing the regional variability of sea ice concentration in summer. SIPN South is a collaborative community project that is hosted on a shared public repository. The forecast and verification data used in SIPN South are publicly available in near-real time for further use by the polar research community, and eventually, policymakers.

Long‐term trajectories of non‐native vegetation on islands globally - Anna Walentowitz; Bernd Lenzner; Franz Essl; Nichola Strandberg; Alvaro Castilla‐Beltrán; José María Fernández‐Palacios; Svante Björck; Simon Connor; Simon G. Haberle; Karl Ljung; Matiu Prebble; Janet M. Wilmshurst; et al. (Ecology Letters, 2023)
Human‐mediated changes in island vegetation are, among others, largely caused by the introduction and establishment of non‐native species. However, data on past changes in non‐native plant species abundance that predate historical documentation and censuses are scarce. Islands are among the few places where we can track human arrival in natural systems allowing us to reveal changes in vegetation dynamics with the arrival of non‐native species. We matched fossil pollen data with botanical status information (native, non‐native), and quantified the timing, trajectories and magnitude of non‐native plant vegetational change on 29 islands over the past 5000 years. We recorded a proportional increase in pollen of non‐native plant taxa within the last 1000 years. Individual island trajectories are context‐dependent and linked to island settlement histories. Our data show that non‐native plant introductions have a longer and more dynamic history than is generally recognized, with critical implications for biodiversity baselines and invasion biology.

Cancer survivorship experiences in Utah: an evaluation assessing indicators of survivors’ quality of life, health behaviors, and access to health services - Morgan M. Millar; Kimberly A. Herget; Blessing Ofori-Atta; Rachel R. Codden; Sandra L. Edwards; Marjorie E. Carter; Brad Belnap; Anne C. Kirchhoff; Carol Sweeney (Cancer Causes & Control, 2023)

Plant phenology drives seasonal changes in shear stress partitioning in a semi-arid rangeland - Nancy P. Ziegler; Nicholas P. Webb; John A. Gillies; Brandon L. Edwards; George Nikolich; Justin W. Van Zee; Brad F. Cooper; Dawn M. Browning; Ericha M. Courtright; Sandra L. LeGrand (Agricultural and Forest Meteorology, 2023)

A roadmap for ladybird conservation and recovery - António O. Soares; Danny Haelewaters; Olga M. C. C. Ameixa; Isabel Borges; Peter M. J. Brown; Pedro Cardoso; Michiel D. de Groot; Edward W. Evans; Audrey A. Grez; Axel Hochkirch; Milada Holecová; Alois Honěk; et al. (Conservation Biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The dangers of misrepresenting wildlife trade: response to Natusch et al. 2021 - David P. Edwards; Neil D'Cruze; Sandra Altherr; Alice Hughes; Jordi Janssen; Vincent Nijman; Stesha A. Pasachnik; Brett R. Scheffers; Chris R. Shepherd; Emerson Sy; Mark Auliya (Conservation Biology, 2021)

Effects of Holocene climate change, volcanism and mass migration on the ecosystem of a small, dry island (Brava, Cabo Verde) - Alvaro Castilla‐Beltrán; Lea de Nascimento; José María Fernández‐Palacios; Robert J. Whittaker; Maria M. Romeiras; Andrew B. Cundy; Mary Edwards; Sandra Nogué (Journal of Biogeography, 2021)
Aim Palaeoecological data provide an essential long‐term perspective of ecological change and its drivers in oceanic islands. However, analysing the effects of multi‐scalar and potentially co‐occurring disturbances is particularly challenging in dry islands. Here, we aim to identify the ecological consequences of the integrated impacts of a regional drying trend, volcanic eruptions and human mass migrations in a spatially constrained environment—a small, dry oceanic island in Macaronesia. Location Brava Island, Republic of Cabo Verde. Taxa Terrestrial vegetation and fungi. Methods We use palaeoecological analyses applied to a caldera soil profile that dates back to 9700 cal yr BP (calibrated years before the present). Analyses include pollen (vegetation history), non‐pollen palynomorphs (changes in fern and fungal communities), grain‐size distribution, loss‐on‐ignition and geochemistry (sedimentology and erosion regimes), microscopic tephra shards (volcanic ash deposition) and charcoal (fire regime). Results A regional drying trend after c. 4000 cal yr BP caused increased erosion but had limited immediate impacts on highland grassland vegetation. The expansion of fern‐rich woody scrubland was contemporaneous with significant deposition of volcanic ash and erosion between 1800 and 650 cal yr BP. About 300 cal yr BP, exogenous plants expanded, grazing and fires increased, and there was a decrease of native vegetation cover. Main conclusions Throughout the Holocene, highland vegetation in Brava was characterized by the presence of open landscapes dominated by herbaceous species (e.g. Poaceae, Forsskaolea ), with some presence of woody native taxa (e.g. Ficus , Dodonaea ). A regional drying trend was a driver of erosion since the Mid Holocene but did not have an immediate influence on highland vegetation. Tephra deposition is a possible driver of vegetation change. Inter‐island mass migration after volcanic events in Fogo Island c. 1680 CE potentially triggered land use change and intensification, causing a reduction of native vegetation in Brava.

Factors determining variation in colour morph frequencies in invasive Harmonia axyridis populations - Alois Honek; Peter M. J. Brown; Zdenka Martinkova; Jiri Skuhrovec; Marek Brabec; Giovanni Burgio; Edward W. Evans; Marc Fournier; Audrey A. Grez; Jan Kulfan; Francesco Lami; Eric Lucas; et al. (Biological Invasions, 2020)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Decrease in 230 Th in the Amundsen Basin since 2007: far-field effect of increased scavenging on the shelf? - Ole Valk; Michiel M. Rutgers van der Loeff; Walter Geibert; Sandra Gdaniec; S. Bradley Moran; Kate Lepore; Robert Lawrence Edwards; Yanbin Lu; Viena Puigcorbé; Nuria Casacuberta; Ronja Paffrath; William Smethie; et al. (Ocean Science, 2020)
This study provides dissolved and particulate 230Th and 232Th results as well as particulate 234Th data collected during expeditions to the central Arctic Ocean (GEOTRACES, an international project to identify processes and quantify fluxes that control the distributions of trace elements; sections GN04 and GIPY11). Constructing a time series of dissolved 230Th from 1991 to 2015 enables the identification of processes that control the temporal development of 230Th distributions in the Amundsen Basin. After 2007, 230Th concentrations decreased significantly over the entire water column, particularly between 300 and 1500 m. This decrease is accompanied by a circulation change, evidenced by a concomitant increase in salinity. A potentially increased inflow of water of Atlantic origin with low dissolved 230Th concentrations leads to the observed depletion in dissolved 230Th in the central Arctic. Because atmospherically derived tracers (chlorofluorocarbon (CFC), sulfur hexafluoride (SF6)) do not reveal an increase in ventilation rate, it is suggested that these interior waters have undergone enhanced scavenging of Th during transit from Fram Strait and the Barents Sea to the central Amundsen Basin. The 230Th depletion propagates downward in the water column by settling particles and reversible scavenging.

An Integrated All-Atlantic Ocean Observing System in 2030 - Brad deYoung; Martin Visbeck; Moacyr Cunha de Araujo Filho; Molly O’Neil Baringer; CarolAnne Black; Erik Buch; Gabrielle Canonico; Paulo Coelho; Janice T. Duha; Martin Edwards; Albert Fischer; Jan-Stefan Fritz; et al. (Frontiers in Marine Science, 2019)

The challenge of incorporating animal welfare in a social life cycle assessment model of European chicken production - Craig W. Tallentire; Sandra A. Edwards; Tommy Van Limbergen; Ilias Kyriazakis (The International Journal of Life Cycle Assessment, 2019)

Magmatic platinum nanoparticles in metasomatic silicate glasses and sulfides from Patagonian mantle xenoliths - José María González-Jiménez; Josep Roqué-Rosell; Abigail Jiménez-Franco; Santiago Tassara; Fernando Nieto; Fernando Gervilla; Sandra Baurier; Joaquín A. Proenza; Edward Saunders; Artur P. Deditius; Manuel Schilling; Alexandre Corgne (Contributions to Mineralogy and Petrology, 2019)

Tipping point in plant–fungal interactions under severe drought causes abrupt rise in peatland ecosystem respiration - Vincent E. J. Jassey; Monika K. Reczuga; Małgorzata Zielińska; Sandra Słowińska; Bjorn J. M. Robroek; Pierre Mariotte; Christophe V. W. Seppey; Enrique Lara; Jan Barabach; Michał Słowiński; Luca Bragazza; Bogdan H. Chojnicki; et al. (Global Change Biology, 2018)
Ecosystems are increasingly prone to climate extremes, such as drought, with long‐lasting effects on both plant and soil communities and, subsequently, on carbon (C) cycling. However, recent studies underlined the strong variability in ecosystem's response to droughts, raising the issue of nonlinear responses in plant and soil communities. The conundrum is what causes ecosystems to shift in response to drought. Here, we investigated the response of plant and soil fungi to drought of different intensities using a water table gradient in peatlands—a major C sink ecosystem. Using moving window structural equation models, we show that substantial changes in ecosystem respiration, plant and soil fungal communities occurred when the water level fell below a tipping point of −24 cm. As a corollary, ecosystem respiration was the greatest when graminoids and saprotrophic fungi became prevalent as a response to the extreme drought. Graminoids indirectly influenced fungal functional composition and soil enzyme activities through their direct effect on dissolved organic matter quality, while saprotrophic fungi directly influenced soil enzyme activities. In turn, increasing enzyme activities promoted ecosystem respiration. We show that functional transitions in ecosystem respiration critically depend on the degree of response of graminoids and saprotrophic fungi to drought. Our results represent a major advance in understanding the nonlinear nature of ecosystem properties to drought and pave the way towards a truly mechanistic understanding of the effects of drought on ecosystem processes.

Oligomer-prone E57K-mutant alpha-synuclein exacerbates integration deficit of adult hippocampal newborn neurons in transgenic mice - Martin Regensburger; Sebastian R. Schreglmann; Svenja Stoll; Edward Rockenstein; Sandra Loskarn; Wei Xiang; Eliezer Masliah; Beate Winner (Brain Structure and Function, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

A conceptual framework for analyzing deltas as coupled social–ecological systems: an example from the Amazon River Delta - Eduardo S. Brondizio; Nathan D. Vogt; Andressa V. Mansur; Edward J. Anthony; Sandra Costa; Scott Hetrick (Sustainability Science, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

The novel mu-opioid antagonist, GSK1521498, reduces ethanol consumption in C57BL/6J mice - Tamzin L. Ripley; Sandra Sanchez-Roige; Edward T. Bullmore; Manolo Mugnaini; Kay Maltby; Sam R. Miller; David R. Wille; Pradeep Nathan; David N. Stephens (Psychopharmacology, 2015)

Functional analysis reveals angiogenic potential of human mesenchymal stem cells from Wharton’s jelly in dermal regeneration - Sandra S. Edwards; Gabriela Zavala; Catalina P. Prieto; Matías Elliott; Samuel Martínez; Jose T. Egaña; María R. Bono; Verónica Palma (Angiogenesis, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Animal health, welfare and production problems in organic pregnant and lactating sows - Sandra Edwards; Helena Mejer; Allan Roepstorff; Armelle Prunier (Organic Agriculture, 2014)

Description of organic pig production in Europe - Barbara Früh; Davide Bochicchio; Sandra Edwards; Lene Hegelund; Christine Leeb; Albert Sundrum; Steffen Werne; Sophia Wiberg; Armelle Prunier (Organic Agriculture, 2014)

Animal health, welfare and production problems in organic weaner pigs - Christine Leeb; Lene Hegelund; Sandra Edwards; Helena Mejer; Allan Roepstorff; Tine Rousing; Albert Sundrum; Marianne Bonde (Organic Agriculture, 2014)

Health, welfare and production problems in organic suckling piglets - Armelle Prunier; Stanislas Lubac; Helena Mejer; Allan Roepstorff; Sandra Edwards (Organic Agriculture, 2014)

Characteristics of organic pig farms in selected European countries and their possible influence on litter size and piglet mortality - Armelle Prunier; Sabine Dippel; Davide Bochicchio; Sandra Edwards; Christine Leeb; Kristina Lindgren; Albert Sundrum; Klaas Dietze; Marianne Bonde (Organic Agriculture, 2014)

Sulfide mineralization associated with arc magmatism in the Qilian Block, western China: zircon U-Pb age and Sr-Nd-Os-S isotope constraints from the Yulonggou and Yaqu gabbroic intrusions - Zhao-Wei Zhang; Wen-Yuan Li; Yong-Bao Gao; Chusi Li; Edward M. Ripley; Sandra Kamo (Mineralium Deposita, 2014)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Toxicity of sediment pore water in Puget Sound (Washington, USA): a review of spatial status and temporal trends - Edward R. Long; R. Scott Carr; James M. Biedenbach; Sandra Weakland; Valerie Partridge; Margaret Dutch (Environmental Monitoring and Assessment, 2013)

Geochronology, petrology and geochemistry of the Nanlinshan and Banpo mafic–ultramafic intrusions: implications for subduction initiation in the eastern Paleo-Tethys - Gangzhu Li; Chusi Li; Edward M. Ripley; Sandra Kamo; Shangguo Su (Contributions to Mineralogy and Petrology, 2012)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Chloroform respiration to dichloromethane by a Dehalobacter population - Ariel Grostern; Melanie Duhamel; Sandra Dworatzek; Elizabeth A. Edwards (Environmental Microbiology, 2010)
Summary Chloroform (CF), or trichloromethane, is an ubiquitous environmental pollutant because of its widespread industrial use, historically poor disposal and recalcitrance to biodegradation. Chloroform is a potent inhibitor of metabolism and no known organism uses it as a growth substrate. We discovered that CF was rapidly and sustainably dechlorinated in the course of investigating anaerobic reductive dechlorination of 1,1,1‐trichloroethane in a Dehalobacter ‐containing culture. Like 1,1,1‐trichloroethane dechlorination in this culture, CF dechlorination was a growth‐linked respiratory process, requiring H 2 as an electron donor and CF as an electron acceptor. Moreover, the same specific reductive dehalogenase likely catalyzed both reactions. This Dehalobacter population appears specialized for substrates with three halogen substituents on the same carbon atom, with widespread implications for bioremediation.

Erratum to: Precise U–Pb zircon–baddeleyite age of the Jinchuan sulfide ore-bearing ultramafic intrusion, western China - Mingjie Zhang; Sandra L. Kamo; Chusi Li; Peiqing Hu; Edward M. Ripley (Mineralium Deposita, 2010)

Precise U–Pb zircon–baddeleyite age of the Jinchuan sulfide ore-bearing ultramafic intrusion, western China - Mingjie Zhang; Sandra L. Kamo; Chusi Li; Peiqing Hu; Edward M. Ripley (Mineralium Deposita, 2010)

Prevalence and predictors of cancer screening among American Indian and Alaska native people: the EARTH study - Mary Catherine Schumacher; Martha L. Slattery; Anne P. Lanier; Khe-Ni Ma; Sandra Edwards; Elizabeth D. Ferucci; Lillian Tom-Orme (Cancer Causes & Control, 2008)

Riverbeds demarcate distinct conservation units of the radiated tortoise (Geochelone radiata) in southern Madagascar - Sébastien Rioux Paquette; Sandra M. Behncke; Susan H. O’Brien; Rick A. Brenneman; Edward E. Louis; François-Joseph Lapointe (Conservation Genetics, 2007)

Spatial Extent Of Degraded Sediment Quality In Puget Sound (Washington State, U.S.A.) Based Upon Measures Of The Sediment Quality Triad - Edward R. Long; Margaret Dutch; Sandra Aasen; Kathy Welch; M. Jawed Hameedi (Environmental Monitoring and Assessment, 2005)

Body mass index and colon cancer: an evaluation of the modifying effects of estrogen (United States) - M.L. Slattery; Rachel Ballard-Barbash; Sandra Edwards; Bette J. Caan; John D. Potter (Cancer Causes & Control, 2003)

CONDITIONALLY IMMORTAL OVARIAN CELL LINES FOR INVESTIGATING THE INFLUENCE OF OVARIAN STROMA ON THE ESTROGEN SENSITIVITY AND TUMORIGENICITY OF OVARIAN SURFACE EPITHELIAL CELLS - FENG JIANG; BEATRIZ O. SAUNDERS; EDWARD HALLER; SANDRA LIVINGSTON; SANTO V. NICOSIA; WENLONG BAI (In Vitro Cellular & Developmental Biology - Animal, 2003)

Conditionally Immortal Ovarian Cell Lines for Investigating the Influence of Ovarian Stroma on the Estrogen Sensitivity and Tumorigenicity of Ovarian Surface Epithelial Cells - Feng Jiang; Beatriz Saunders; Edward Haller; Sandra Livingston; Santo Nicosia; Wenlong Bai (In Vitro Cellular & Developmental Biology - Animal, 2003)

Conditionally Immortal Ovarian Cell Lines for Investigating the Influence of Ovarian Stroma on the Estrogen Sensitivity and Tumorigenicity of Ovarian Surface Epithelial Cells - Feng Jiang; Beatriz Saunders; Edward Haller; Sandra Livingston; Nicosia Santo; Wenlong Bai (In Vitro Cellular & Developmental Biology - Animal, 2003)

Associations between family history of cancer and genes coding for metabolizing enzymes (United States) - Martha L. Slattery; Sandra L. Edwards; Wade Samowitz; John Potter (Cancer Causes & Control, 2000)

Colon cancer screening, lifestyle, and risk of colon cancer - Martha L. Slattery; Sandra L. Edwards; Khe Ni Ma; Gary D. Friedman (Cancer Causes & Control, 2000)

A prospective study of plasma ascorbic acid concentrations and breast cancer (United States) - Kana Wu; Kathy J. Helzlsouer; Anthony J. Alberg; George W. Comstock; Edward P. Norkus; Sandra C. Hoffman (Cancer Causes & Control, 2000)

Hormone replacement therapy and improved survival among postmenopausal women diagnosed with colon cancer (USA) - Martha L. Slattery; Kristin Anderson; Wade Samowitz; Sandra L. Edwards; Karen Curtin; Bette Caan; John D. Potter (Cancer Causes & Control, 1999)

The maize retinoblastoma protein homologue ZmRb-1 is regulated during leaf development and displays conserved interactions with G1/S regulators and plant cyclin D (CycD) proteins - Rachael Huntley; Sandra Healy; Donna Freeman; Paul Lavender; Sarah de Jager; Judith Greenwood; Joe Makker; Edward Walker; Mark Jackman; Qi Xie; Andrew J. Bannister; Tony Kouzarides; et al. (Plant Molecular Biology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abscisic acid signal transduction in epidermal cells of Pisum sativum L. Argenteum : both dehydrin mRNA accumulation and stomatal responses require protein phosphorylation and dephosphorylation - Sandra J. Hey; Andrea Bacon; Edward Burnett; Steven J. Neill (Planta, 1997)

Hormone replacement therapy, reproductive history, and colon cancer: a multicenter, case-control study in the United States - Ellen Kampman; John D. Potter; Martha L. Slattery; Bette J. Caan; Sandra Edwards (Cancer Causes & Control, 1997)